Chiryvy Rendyju, menino brilhante: identidade e emancipação de jovens guarani kaiowá em práticas de comunicação midiática - Souza, Ana Maria Melo e (2018)
This research seeks to understand the media communication practices carried out by Guarani Kaiowá indigenous youths in villages located in Mato Grosso do Sul, which use audiovisual technologies such as photography and video as ways of narrating their history in the current context of social and cultural movements experienced by their groups and the movements for the conquest of original territories. It involves the appropriation of a new language on the production of documentaries that spreads information, awakens reflections within communities, expands networks of relations with other groups and promotes their ethnic reassertion. Guided by Social Psychology, the life narrative of the indigenous Chiryvy Rendyju leads us to an understanding of the Kaiowá Guarani identity, revealing its metamorphoses and search for autonomy and emancipation